2020
DOI: 10.1016/j.celrep.2020.107664
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitylation of the ER-Shaping Protein Lunapark via the CRL3KLHL12 Ubiquitin Ligase Complex

Abstract: Highlights d A proteomic approach to identify CRL substrates ubiquitylated at cellular membranes d The ER shaping protein Lunapark is ubiquitylated by the CRL3 KLHL12 ubiquitin ligase d Lunapark binds mTOR and its ubiquitylation affects lysosomal recruitment of mTORC1 d Inhibition of Lunapark ubiquitylation leads to neurodevelopmental defects

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 61 publications
2
13
0
Order By: Relevance
“…D). Similar results were obtained when a mutant form of ubiquitin (UbK0), which allows only mono‐ubiquitination due to the lack of lysine residues, ( 38 ) was used instead of WT ubiquitin (Supporting Fig. E).…”
Section: Resultssupporting
confidence: 78%
“…D). Similar results were obtained when a mutant form of ubiquitin (UbK0), which allows only mono‐ubiquitination due to the lack of lysine residues, ( 38 ) was used instead of WT ubiquitin (Supporting Fig. E).…”
Section: Resultssupporting
confidence: 78%
“…A recent study showed that LNP uses a Pro-rich motif to bind KLHL12 (Yuniati et al, 2020), an observation that we confirmed (Figure 4A). PEF1 possesses a similar Pro-rich sequence in its amino-terminal domain, which is required for recognition by KLHL12 (Figure 4A) and for restoring CUL3 KLHL12 assembly in DPEF1 cells (Figure 4B).…”
Section: Pef1 Interactions With Cul3 Klhl12supporting
confidence: 89%
“…At the same time, PEF1 deletion promoted the interaction of KLHL12 with Lunapark (LNP) (Figure 2A), an ER membrane protein that was not detected in CUL3 KLHL12 -PEF1-ALG2 enzymes (Figure 2B). While we and others had noted LNP in complexes of overexpressed KLHL12 (McGourty et al, 2016;Yuniati et al, 2020), these findings suggested that endogenous LNP preferentially interacts with KLHL12 molecules that are not engaged with co-adaptor or CUL3.…”
Section: Lnp Is a Candidate Crl3 Assembly Inhibitormentioning
confidence: 49%
“…5). While Atlastins, Rtn3, and Lunapark have been previously linked to autophagy (49)(50)(51)(52), the connection of NOMO1 and Climp63 to the autophagic/lysosomal route is to our knowledge underexplored and warrants closer scrutiny in the future.…”
Section: Discussionmentioning
confidence: 98%